Design and performance of a modular combined cycle solar power plant using the fluidized particle solar receiver technology. (15th September 2020) - Behar, Omar; Grange, Benjamin; Flamant, Gilles
Graphical abstract: Highlights: A medium size solar power plant with particles receiver and direct energy storage is designed. A practical technique is used to model each component of the plant. The thermal efficiency of the combined cycle reaches 46%. The solar-to-electric efficiency reaches 25.8% and 24.7% in hybrid and only-solar modes. Solar share reaches 73.7% in hybrid mode thanks to the low inlet temperature of the gas turbine. Abstract: The design and the performance of a medium-scale modular solar power plant ( 20 MW) integrating a gas turbine combined cycle with a fluidized particle-in-tube receiver and direct thermal storage are investigated in this paper. A practical technique is used to design each part of the solar power plant. The complete design starts with the solar gas turbine (SGT) since it defines the necessary power to run it; then, the other parts are designed upstream. Three different cases are investigated under different operation strategies corresponding to two particle temperatures 750 °C and 880 °C, and hybrid and solar-only operation modes respectively. The results show that the nominal efficiency of the components including the heliostat field, the solar receiver, the gas turbine, and the steam turbine can reach 67%, 80%, 32%, and 34.5% respectively. As a result, the nominal thermal efficiency and the annual capacity factor of the complete solar power plant achieve 46% and 33.47% respectively. The overall nominal efficiency (solar-to-electric efficiency) of the plant for hybrid operation mode is 25.80%. It varies from 21.16% to 24.7% for the solar-only operation mode. Special interest is shown to the part-load operations.